The Chester Beatty Biblical Papyri at Ninety : Literature, Papyrology, Ethics. - Allen, Garrick Vernon. (Manuscripta Biblica Series, 2023)
Manuscripta Biblica is dedicated to scholarship on manuscripts of the Jewish and Christian Bible. The series is open to all fields and methods that address biblical manuscripts in a broad sense. This includes research on textual and paratextual aspects, the presentation, organization, physical composition, and artistic dimensions of the artifact as well as issues related to production, dissemination, forms of use, and reception.